Analysis of USAID/Georgia Supported Basic Education Program First Cycle Implementation: (Akaki Tsereteli State University Pedagogical Faculty Case) - Akhvlediani, Maia; Kobuladze, Nato; Moralishvili, Sophio (Forum Pedagogiczne, 2021)
The article highlights Akaki Tsereteli State University's involvement and participation in wide school reforms to establish student-centered education in Georgia. School educational reform cannot proceed and succeed without the direct involvement of the universities which carry out teacher preparation programs. Unequivocally, there should be close cooperation and collaboration between these two institutions to reach the desirable and targeted outcomes. The purpose of the article was to present the results of the survey, which was intended to assess the effectiveness of training conducted by the university trainers during the first phase of the new school reform in Georgia which focused on achieving student-centered learning. The selected trainers from the eight partnering universities were supposed to cover 2075 schools throughout Georgia (373 schools in Imereti Region) to train leader teachers and help the institution to develop new instructional methods, more specifically, to develop a school curriculum based on constructivist educational principles and apply it into practice. The survey findings assisted Pedagogical faculty in identifying existing curriculum gaps and discrepancies and taking measures to bridge them by modifying and supplementing them with the necessary content.